Pictures as a Learning Media in Teaching Vocabulary - Nihta Vera Frelly Liando; Devilito Prasetyo Tatipang; Grandy Tamboto; Maria Poluan; Maissy Manuas (Universitas Batanghari Jambi, 2022)
Technological developments in the current era provide many conveniences and benefits for various agencies, including educational institutions. Teachers as one part of educational institutions really need to take advantage of technological developments as a means or media in teaching so that learning does not seem boring. In fact there are many teachers who often focus on books oriented. This causes the students’ learning process to be not optimal, especially in learning foreign languages such as English. Of course, if learning only focuses on books, it will make students feel bored and lazy to learn English. Vocabulary as one of the important aspects in English cannot be taught with books alone, because in learning it requires interesting media to be able to make students more enjoy and interested in learning vocabulary. Based on this, this study aims to determine whether using pictures as learning can improve the vocabulary of students. This study used a pre-experimental design with one group pre-test and post-test. The research subject is class VII with the research instrument is a test. In analyzing the data, in this study the mean score formula was implemented. The results showed that picture as a learning medium greatly affects student learning outcomes in terms of vocabulary. Where, there was a significant increase in students' vocabulary after using pictures as treatment. Picture itself makes students more enthusiastic in learning because the pictures used attract students' attention. Finally, this research also explains the potentials that can be used or developed in the future.